Kompetensi Sosial Guru Pendidikan Agama Kristen Dalam Meningkatkan Ranah Afektif Siswa - Lian Lian; Rinto Hasiholan Hutapea; Isabella Jeniva (Harati: Jurnal Pendidikan Kristen, 2023)
The purpose of this study was to determine the social competence of Christian Religious Education teachers in improving the affective domain of students in class XI MIA 1 SMA Negeri 1 Manuhing. The research method used in this research is descriptive qualitative. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study stated that the social competence of PAK teachers in class XI MIA 1 SMA Negeri 1 Manuhing is very important so that Christian Religious Education teachers can manage emotions when teaching in class, can understand students in class, can provide positive self-identity for students, can increase knowledge and understanding school culture, can adopt social values, can behave and act objectively, can adapt to students in class, and can build good communication relationships with students in class. Then, the social competence of Christian Religious Education teachers in improving the affective domain of students in class XI MIA 1 SMA Negeri 1 Manuhing, namely the teacher builds good communication relationships and understands students with students, understands students' emotions, and tries to help students to be able to live according to values and Christian character.